Recent Developments in Heterogeneous Selective Hydrogenation of Halogenated Nitroaromatic Compounds to Halogenated Anilines - Pietrowski, Mariusz (Current Organic Synthesis, 2012)
Selective catalytic reduction of halogenated nitroaromatic compounds is the most widely used method for the synthesis of halogenated anilines, important intermediates in the chemistry of pesticides, herbicides, drugs, pigments and dyes. This review reports progress made in the last decade in the field of hydrogenation of halogenated nitro arenes with the use of heterogeneous catalysts. The first sections of the review contain a concise report on applications of halogenated anilines, methods for their preparation and reaction pathways for hydrogenation of haloaromatic nitro compounds. Subsequent sections discuss hydrogenation properties of platinum group metals, new catalysts based on gold and silver as well as nickel catalysts. Particular attention is paid to positive effects of the use of new unconventional supports and catalyst preparation methods. Finally, an attempt is made at systematising the most important factors affecting high activity and selectivity of heterogeneous catalysts for selective reduction of haloaromatic nitro compounds.
Keywords: green chemistry